Spectrophotometric Method for Quantitative Determination of the Amount of Flavonoids in Oil Extract - Mirzalieva G.A.; Pulatova F.A.; Kamilov Kh.M. (Scientific Trends, 2025)
This paper presents the results of research on the development of a UV spectrophotometric method for the quantitative determination of total flavonoids in an oil extract obtained from a mixture of medicinal plant crudes. A method is proposed for extract sample preparation with saponification and transfer of the flavonoid fraction to 80% ethanol, followed by a complexing reaction with AlCl3 and photometric measurement at 415 nm. Total flavonoids were quantified based on rutin. The amount of flavonoids in oil extract samples varied within the range of 8.17-9.05 mg/g. The method can be used for quality control of the oil extract.
Keywords: extraction, oil extract, flavonoids, spectrophotometry, quantitative analysis, plant raw materials.